Influences of Family Functioning, Emotional Quotient, Social Support on Helping Behaviors of the Young Volunteer Spirit: A Case Study of Community Hospitals in Nonthaburi Province - Saroj, Wannapha; Piolueang, Ngamlamai (Journal of Health Science of Thailand, 2018)
The objectives of this research were to study: 1) the level and influences of the family functioning, emotional quotient and social support of the young volunteer spirit students; on their helping behavior. The data were collected 426 from young volunteer-spirit students in five community hospitals in Nonthaburi province. The statistical methods were percentage, mean, standard deviation and stepwise multiple regression analysis. The results were as follow: 1) the young volunteerspirit students in the community hospitals in Nonthaburi province had perceived their family functioning, emotional quotient, social support and had helping behavior at high levels; 2) the factors including; emotional quotient in handling relationships dimension, family functions in behavior control dimension, social support in information from school, and emotional quotient in managing emotions dimension, family functioning in emotional support from school, the counting of siblings and their education had influenced on helping behavior at the 0.001 level of significance with the possibility at 65.2 percents (R2adj 0.652). Especially, emotional quotient in managing emotions dimension was the best predictor among those to factors analyzed.